Regstellende aksie: ’n etiese perspektief - Kruger, S. (Koers, 1995)
Affirmative action: an ethical perspective. The scrapping of certain relevant laws of the apartheid era can not immediately undo the wrongs of apartheid. What is essentially needed is compensation of some kind for every individual or group who has been affected by it. The question is whether affirmative action can be ethically justified; is it inherently 'right or wrong’? In this paper different approaches to affirmative action and the normal phases of implementation of affirmative action are investigated. The best known ethical theories are then used to adjudicate the relevance ami ethical justification of affirmative action. In the final analysis six different levels of ethical decision-making are considered. The conclusion arrived at is that affirmative action is unavoidable but that there are a number o f pitfalls awaiting the unwary. To implement affirmative action successfully certain prerequisites must be met.